The interaction of Na atoms with the molecular surfaces H₂O and CH₃OH: the role of delocalized Na3s electrons - Borodin, A.; Hofft, O.; Kahnert, U.; Kempter, V.; Allouche, A. (Физическая инженерия поверхности, 2003)
The interaction of Na atoms with H₂O and CH₃OH films is studied with metastable impact electron spectroscopy (MIES) under UHV conditions. The films were grown at 90 (+/ – 10) K on tungsten substrates, and exposed to Na. Na – induced water dissociation takes place whereby OH and CH₃O – species are formed, and Na – atoms become ionized. At small Na exposures the outermost solvent layer remains largely intact as concluded from the absence of MIES signals caused by the reaction products. However, emission from OH and CH₃O – species, located at the film surface, occurs at larger exposures. In the same exposure range also emission from Na3s – ionization can be detected. The corresponding spectral structure occurs at an energetic position different from that found on metals or semiconductors. For the (Na – water) system the results are compared with First – Principles calculations on (Na)₂(H₂O)₁₀ clusters concerned with the electron and proton exchange within the cluster. Experiment and theory agree in the energetic positions of the main spectral features from water and sodium ionization. The calculations suggest that the 3sNa emission observed experimentally is due to the ejection of solvated 3s electrons which are trapped between the Na – core and water molecules of the surrounding water shell. The simultaneous emergence of dissociation products, OH and CH₃O, and solvated 3s electrons suggests that the delocalization and, consequently, the solvation plays an important role in the Na – water (methanol) reaction. Keywords: metastable impact electron spectroscopy (MIES), water, methanol, ice, solvation, alkali.